Selective and interactive effects of D2 receptor antagonism and positive allosteric mGluR4 modulation on waiting impulsivity. (1st September 2017) - Isherwood, Sarah N.; Robbins, Trevor W.; Nicholson, Janet R.; Dalley, Jeffrey W.; Pekcec, Anton
Abstract: Background: Metabotropic glutamate receptor 4 (mGluR4) and dopamine D2 receptors are specifically expressed within the indirect pathway neurons of the striato-pallidal-subthalamic pathway. This unique expression profile suggests that mGluR4 and D2 receptors may play a cooperative role in the regulation and inhibitory control of behaviour. We investigated this possibility by testing the effects of a functionally-characterised positive allosteric mGluR4 modulator, 4-(( E )-styryl)-pyrimidin-2-ylamine (Cpd11), both alone and in combination with the D2 receptor antagonist eticlopride, on two distinct forms of impulsivity. Methods: Rats were trained on the five-choice serial reaction time task (5-CSRTT) of sustained visual attention and segregated according to low, mid, and high levels of motor impulsivity (LI, MI and HI, respectively), with unscreened rats used as an additional control group. A separate group of rats was trained on a delay discounting task (DDT) to assess choice impulsivity. Results: Systemic administration of Cpd11 dose-dependently increased motor impulsivity and impaired attentional accuracy on the 5-CSRTT in all groups tested. Eticlopride selectively attenuated the increase in impulsivity induced by Cpd11, but not the accompanying attentional impairment, at doses that had no significant effect on behavioural performance when administered alone. Cpd11 also decreased choice impulsivity on the DDT (i.e. increased preference for the large, delayed reward) and decreased locomotor activity. Conclusions: These findings demonstrate that mGluR4s, in conjunction with D2 receptors, affect motor- and choice-based measures of impulsivity, and therefore may be novel targets to modulate impulsive behaviour associated with a number of neuropsychiatric syndromes. Highlights: Positive allosteric mGluR4 modulation increases motor impulsivity and impairs aspects of visual attention. Positive allosteric mGluR4 modulation decreases choice impulsivity as well as indices of motor function. Blocking D2 receptors selectively attenuates the effect of positive allosteric mGluR4 modulation on motor impulsivity.